Development of mechanical pathway cleaner / Ahmad Adham Irfan Nasrullah - Nasrullah, Ahmad Adham Irfan (2023)
Nowadays, almost all of pathway cleaner out there is fueled by either petrol or diesel. If the workers are cleaning the pathway during peak hour, the people who walk around the pathway will be uncomfortable because of the smell coming from the smoke of the usual pathway cleaners that they are using. This fabrication of mechanical pathway cleaner will benefit both of the parties above since it is very environmental- friendly. Basically, the mechanical pathway cleaner will look like a usual lawn mower. The work mechanism of this project is there will be a bigger sprocket connected at the rear tyre rod and a smaller sprocket connected to brush rod. The chain attached to the sprocket will rotate the brush when the pathway cleaner move forward. The rotating brush will collect the dried leaves and rubbish. It comes with a removable collector made from metal sheet and this will ease the user to dump the collected rubbish at any desired place.